The Effect of Flow Factor on Brand Attitude and Purchase Intention in Mobile Legend: Bang-Bang - Anandya, Dudi; Darsono, Brilliant Prabowo Agung; Indarini (Journal of Entrepreneurship and Business, 2023)
Purpose: This research aims to analyze the influence of flow antecedents, which can elicit brand attitudes and purchase intentions. Method: By design, this research is included in causal research, which aims to examine causal relationships between variables. The scale used is an interval of 7 points. The target population is active mobile legends: Bang-bang players who play at least two games daily. The player must have purchased at least two items in the last six months and be 17 years old. Purchase decisions must be made with the player's considerations. The number of samples collected was 300 respondents. The sampling technique used is non-probability sampling with a purposive sampling method. The analysis technique used is structural equation modeling with two stages. The analysis technique used is structural equation modeling with two stages. Hypothesis testing uses a t-test with an alpha of 10%. Result: Only skills that do not contribute to the formation of flow. This result is in line with previous research, so the role of skill as an antecedent needs to be studied further. Flow has been shown to shape brand attitudes and purchase intentions.